2002
DOI: 10.1590/s0100-69912002000400004
|View full text |Cite
|
Sign up to set email alerts
|

O tubo gástrico isoperistáltico no tratamento paliativo do câncer do esôfago

Abstract: 202 INTRODUÇÃOO câncer do esôfago é a sexta neoplasia mais comum 1 e o carcinoma espinocelular apresenta uma prevalência mundial de 3 a 19:100.000 habitantes 2 . Seu tratamento constitui-se em um grande desafio 3 . O diagnóstico da doença é freqüentemente tardio com predomínio de pacientes nos estádios III e IV, quando a cura é impossível 4 . Estima-se que, em nosso país, aproximadamente 8.941 novos casos de câncer de esôfago foram diagnosticados no ano 2000 segundo o INCA/Ministé-rio da Saúde 5 .As populações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
3
2
Order By: Relevance
“…The frequency of undernutrition shown in this study is lower than consulted literature (11,27) . Esophageal obstruction can be the most evident cause of PEU due to the progressive deficit, until the absence of oral route feeding.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The frequency of undernutrition shown in this study is lower than consulted literature (11,27) . Esophageal obstruction can be the most evident cause of PEU due to the progressive deficit, until the absence of oral route feeding.…”
Section: Discussioncontrasting
confidence: 74%
“…Oka et al (20) showed the presence of advanced stage (II & IV) tumors in 60% of patients and Gagliardi et al (14) in 53.4%; these studies did not prioritize patients with removable tumors, as in this investigation. Therefore the percentage of advanced malignant esophagus disease in this study is much higher than in consulted literature and only lower than exclusively palliative studies where all patients had stage III & IV (11) . The high frequency of smoking and habitual drinking was similar to the other consulted studies.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations